Budapest retró 2: Életképek a 60-as, 70-es évekből . Budapest Retro 2: Pictures from the 60's and 70's - Papp, Gábor Zsigmond (Hungary, 2003)
Duration: 01:30:00 The film which contains only archival footage shows how people lived in Budapest for twenty years, in the 60s and the 70s. They reflect the imprint of the Kádár era in clothing, hairstyle and behavior. Cinema ads, commercials, short films as well as the shops and the streets, illustrate how people living in Budapest ate, dressed, and had fun. The film also induces a slight nostalgia while presenting famous relics such as the scooter Panni, the Modex coat, the Varia furniture or the simple black Twist sweater.